Penerapan Konsep Konstitusi Hijau (Green Constitution) di Indonesia Sebagai Tanggung Jawab Negara Dalam Perlindungan dan Pengelolaan Lingkungan Hidup - Maret Priyanta (The Constitutional Court of the Republic of Indonesia, 2010)
Global environmental issue related to state responsibility in protection and management of environment is consider by a develop and development state earlier. The new concept related to it is regulate environment right in constitution. Green Constituion concept is on of solution for answering the concern by a people to environmental function degradation. Indonesia already regulate the environmental issues in constitution as human right. As a comparation study, a republic of Ecuador is one of the state famous as a first state which put the protection of environment in the constitution.Provision of protection and management of environment in Indonesia must regulate in clear in Indonesia Constitution, a lot of human activity cause the degradation and pollution that threat the human being and the next generation. The change of Indonesia Constituion is one of solution for praotection of environment in the future, so the law and other regulatin will be source to the constituion and oriented to the preservation of environment function.